Pattern of electrolyte imbalance and their response to corticosteroid therapy in stroke patients admitted in a tertiary care hospital (Bangladesh Journal of Medicine, 2018)
This prospective, single center, case-control study was designed to see the response of electrolyte imbalance in admitted stroke patients receiving corticosteroid therapy in a tertiary care hospital. In IPD, still in many cases of stroke with cerebral edema, injectable corticosteroids are given frequently. Our aim was to find out the common electrolyte imbalances in different type of acute stroke, and, if there was any difference between the patterns of electrolyte imbalance in patients receiving corticosteroids for management, with those who did not receive.Methods: The source population of this study comprised stroke patients attending the DMCH, between 1st January to 30th June 2014. Total 70 patients, 35 as control and 35 as case group, who received steroids, were randomly enrolled for the study. Detail demographic data were collected from the informant was recorded in structured case report form.Result: In our study, 48 (68.55%) patients had infarction and 22 (31.45%) patients had hemorrhagic stroke. Hyponatremia was detected in majority 51 (72.85%), others imbalances are hypernatremia 9(12.85%), hypokalaemia 31(44.28%), hyperkalaemia 2(2.85%) and hypochloraemia 37(52.85%). Out of 48 ischemic stroke, hypernatraemia, hypokalaemia and hypochloraemia was present among 8(16.66%), 19(39.58%) and 24(50%) patients respectively. Out of 22 haemorrhagic stroke patients, 1(4.54%), 12(54.54%), 2(9.09%) and 13(59.09%) cases were found to have hypernatraemia, hypokalaemia, hyperkalaemia and hypochloraemia respectively. After giving injectable steroids, differences were statistically significant between two group, p-value was 0.016 (p